Etxe jako baskijskie „słowo-klucz” - Mirgos, Katarzyna (Studia Europaea Gnesnensia, 2011)
This paper is concerned with the interpretation of a Basque notion of etxe (“home”) in the context of the concept of keywords in the process of culture discovery. Ac-cording to the author, the word is an essential constituent in the Basque worldview, while its analysis yields interesting observations regarding the cultural specificity of the Basques.